Moving towards Inclusive Education for All: Examining Stakeholder Perceptions of Educating Students with Special Needs in Schools Operated by the Jordan Field of the UNRWA. Issue 2 (4th March 2021) - Rodriguez, Jacqueline
ABSTRACT: Perceptions of inclusive education in schools operated by the Jordan field of the United Nations Relief and Works Agency for Palestine Refugees in the Near East were explored through multiple embedded case studies. Each of the three schools examined included a student with a special educational need. The study was framed by a theoretical model of inclusive education and guided by theoretical propositions, an empirical hypothesis developed using previous research. Findings from interviews, classroom observations, and document reviews suggest that all stakeholders believe education for students with special educational needs is a human right. However, perceptions of inclusion differed based on several factors including the student's level of need and the perceived severity of the disability, the teacher's self-efficacy and feeling of preparedness towards meeting the needs of students, and the impact of overcrowded classrooms and limited instructional time.